2020
DOI: 10.3389/fncel.2020.591874
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, a Regulated Neuronal Cell Death Type After Intracerebral Hemorrhage

Abstract: Ferroptosis is a term that describes one form of regulated non-apoptotic cell death. It is triggered by the iron-dependent accumulation of lipid peroxides. Emerging evidence suggests a link between ferroptosis and the pathophysiological processes of neurological disorders, including stroke, degenerative diseases, neurotrauma, and cancer. Hemorrhagic stroke, also known as intracerebral hemorrhage (ICH), belongs to a devastating illness for its high level in morbidity and mortality. Currently, there are few esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 71 publications
2
46
0
2
Order By: Relevance
“…Emerging data suggest that ferroptosis contributes to ICH-induced secondary brain injury and might be one of most influential cell death types after ICH (4,5,16). Therefore, therapy that targets the inhibition of ferroptosis may effectively prevent neuronal death, thereby reducing secondary brain injury after ICH (17). 20-Hydroxy-5,8,11,14-eicosatetraenoic acid (20-HETE) plays an important role in regulating a wide variety of normal physiological functions as well as the pathogenesis of diverse disease conditions (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data suggest that ferroptosis contributes to ICH-induced secondary brain injury and might be one of most influential cell death types after ICH (4,5,16). Therefore, therapy that targets the inhibition of ferroptosis may effectively prevent neuronal death, thereby reducing secondary brain injury after ICH (17). 20-Hydroxy-5,8,11,14-eicosatetraenoic acid (20-HETE) plays an important role in regulating a wide variety of normal physiological functions as well as the pathogenesis of diverse disease conditions (18).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggest that ferroptosis contributes to ICH-induced secondary brain injury and might be one of most influential cell death types after ICH ( 4 , 5 , 16 ). Therefore, therapy that targets the inhibition of ferroptosis may effectively prevent neuronal death, thereby reducing secondary brain injury after ICH ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is amassing which connects the pathways underlying ferroptosis to neurological pathologies such as Alzheimer's disease, Parkinson's disease, Huntington's disease and amyotrophic lateral sclerosis (Zille et al 2019;Devos et al 2019;Masaldan et al 2019;De Gregorio-Rocasolano et al 2019). Furthermore, data from experiments have implied that ferroptosis also arises in haemorrhagic cerebrovascular accidents (Bai et al 2020;Li et al 2017a, b, c;Zhang et al 2018a, b;Guo et al 2020). It was demonstrated that surplus quantities of iron were released following the degradation of haemoglobin after the development of an intracerebral haematoma.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that large amounts of ferrous ions are transported to neurons by transferrin, which triggers a Fenton reaction and produces a large number of ROS, resulting in neuronal cell death. Currently, methods to monitor ferroptosis rely mainly on measuring ROS production, lipid peroxidation, iron accumulation, and abilities of ferroptosis inhibitors to block cell death [34][35][36]. According to the previous research results, the ferroptosis inhibitors, ferrostatin-1 and liproxstatin-1, have shown their therapeutic value in animal models of ICH; however, their "ROS inhibitor" roles hinted that they may inhibit other pathways of cell death at the same time [37][38][39].…”
Section: Discussionmentioning
confidence: 99%